2002
DOI: 10.1152/japplphysiol.01095.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of lung inflammatory mediators as a cause of exercise-induced arterial hypoxemia in young athletes

Abstract: We examined whether lung inflammatory mediators are increased during exercise and whether pharmacological blockade can prevent exercise-induced arterial hypoxemia (EIAH) in young athletes. Seventeen healthy athletes (9 men, 8 women; age 23 +/- 3 yr) with varying degrees of EIAH completed maximal incremental treadmill exercise tests after administration of fexofenadine, zileuton, and nedocromil sodium or placebo in a randomized double-blind crossover study. Lung function, arterial blood gases, and inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…It is unlikely that the lower in the NEIAH subjects was due to prematurely terminating exercise, as they became equally acidaemic and had a respiratory exchange ratio over 1.05. Others have shown that airway reactivity and lung inflammatory mediators are not linked to EIAH in young healthy subjects (Wetter et al 2001, 2002). As such, this probably does not explain the discrepancy between groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the lower in the NEIAH subjects was due to prematurely terminating exercise, as they became equally acidaemic and had a respiratory exchange ratio over 1.05. Others have shown that airway reactivity and lung inflammatory mediators are not linked to EIAH in young healthy subjects (Wetter et al 2001, 2002). As such, this probably does not explain the discrepancy between groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to the pulmonary injury evoked airway inflammatory mediator release hypothesis (Pre´faut et al 1997(Pre´faut et al , 2000, an exaggeration of the arterial hypoxemia would be expected with increasing exercise duration as structural changes in the blood-gas barrier (Schaffartzik et al 1993;West et al 1993) intensify over time. Despite considerable appeal of this hypothesis (Pre´faut et al 1997(Pre´faut et al , 2000, the findings of Wetter et al (2001Wetter et al ( , 2002 in exercising human subjects did not lend credence to it. Similarly, pretreatment of thoroughbred horses with dexamethasone for 3 days to suppress the airway inflammatory response, and with a potent antihistaminic agent (H1-receptor antagonist, tripelennamine HCl) to mitigate the effects of airway inflammatory/mast cell released histamine on pulmonary capillary permeability also did not support the pulmonary injury hypothesis for exercise-induced arterial hypoxemia in racehorses (Manohar et al 2002a, b).…”
Section: Discussionmentioning
confidence: 95%
“…8 12 13 However, nedocromil sodium was found to have no effect on pulmonary gas exchange in aerobically fit men and women when administered in conjunction with fexofenadine hydrochloride (a peripheral H 1 receptor antagonist) and zileuton (a leukotriene inhibitor). 10 A recent study has examined the effects of a single dose of a long or short acting ß 2 agonist (formoterol and salbutamol respectively) on trained non-asthmatic subjects during cycle ergometer exercise to exhaustion. 9 No significant differences were found for any maximal exercise variables (workload, VO 2 , VE, and SaO 2 ) between the two drugs or the placebo condition.…”
Section: Discussionmentioning
confidence: 99%
“…8 Anti-inflammatory drugs have been administered immediately before exercise, and the effects on EIAH observed. [8][9][10] To our knowledge, a combination of bronchodilators and corticosteroid drugs, used daily to suppress lung inflammation and reverse bronchoconstriction, has not been used to attenuate EIAH in athletes who experience this condition. Fluticasone is a corticosteroid that inhibits production of inflammatory cells (mast cells, basophils, lymphocytes) and cytokines.…”
mentioning
confidence: 99%